Peran Humas dalam Meningkatkan Citra Sekolah - Wakhidah, Umi Sarifatul; Nina, Oktarina (Universitas Negeri Semarang, 2024)
Challenges for educational institutions can be characterized by increasing institutional competition and the number of educational institutions offering services. The number of existing institutions causes the high competitiveness of each institution. Educational institutions must build a good brand image to influence prospective students and the public to choose the educational institution. Branding image reflects the quality of superior educational institutions, good academic programs, qualified educators, and supporting facilities and infrastructure. The formulation of the problem in this literature review is what is the role of public relations in improving school image and how is the public relations strategy in improving school image. The writing of this article uses a literature study approach that explores information and processes research materials through recorded events that have been reviewed in scientific works in the form of writings, images, or monumental works of a person. The data sources studied were books, journals, magazines, documents, newspapers, research report articles, and information sourced from the internet. Public relations is a comprehensive and integrated strategy regarding the main activities of an institution. In this context, Public Relations is required to be able to shape the values of understanding attitudes to public behavior to be in line with the needs of the institution. The strategy used in packaging public communication messages that contain more about what and who and what are the benefits of the existence of an institution. This ability needs to be supported by public relations programs and activities, especially in order to build the image of educational institutions in the eyes of the community, which consists of marketing and corporate programs and activities. The role of public relations in educational institutions, at least, consists of several roles, namely: communicator, expert advisor, intermediary / counseling, and problem-solving facilitator.